Constelação familiar no poder judiciário brasileiro: humanização do Direito e ampliação da cidadania nos tribunais de justiça multiportas - Valadares, Gilson Coelho (Universidade Federal do Tocantins, 2020)
The study talks about the theme of Family Constellation applied in the Judiciary, specifically in the courts of justice of Brazil. The Family Constellation is a psychotherapeutic method systematized by Bert Hellinger,whose purpose, through representations and images, to find the most appropriate order of love for a given family system or other human grouping system, under the pillars of three major systemic laws universally applicableto family arrangements and their transgenerational connections: Law of Belonging, Law of Hierarchy and Law of Balance.The general objective of the research is to understand the method and its application in the Judiciary, in addition to mapping the diagnostic situation of Brazilian courts of justice. For this purpose, the investigative trajectory used deductive logic, with qualitative and quantitative approach, and developed in two dimensions: theoretical and empirical. Theoretical exploratory research taked place in two phases. The firstbegins a theoretical introduction to the method, in the light of Bert Hellinger's theory; in the second, an interdisciplinary study of the unprecedented application of the Family Constellation in the Brazilian Judiciary and Systemic Law is undertaken, with the theoretical contribution of the creator of the concept of Systemic Law, Judge Sami Storch. In the empirical dimension, the research conducted a diagnostic survey on which and in what situations the courts of justice in Brazil adopt the institute, in order to understand the contribution of Hellinger's practice to social pacification, to the humanization of law and to the expansion citizenship in multiport courts, in addition to acquiring practical-theoretical basis to propose to the Tocantins State Court of Justice the implantation of the Family Constellation in the forensic routine of the county of Palmas-TO, as a pilot project to be replicated to the other counties of State. The results show that, except for the courts of justice of Tocantins, Sergipe, Espírito Santo, Acre, Amazonas and Roraima, the other 78% already apply, in some measure, the psychotherapeutic technique of the Family Constellation in family matters, surchas divorce, alimony, child custody, stable union, inventory, adoption, among others; on some criminal matters; in prisons; in cases of domestic violence and of childhood and youth; in some civil cases, involving elderly, bankruptcies and over-indebted; in cases of the second degree of jurisdiction. As secondary results, the study identifies the chronology of the implementation of the institute in each state; the type of bond of the constellators; the lack of general statistics on the impacts achieved and the lack of institutionalization of the method as a public policy in all courts surveyed.The research concluded that, despite the rapid advance in the application of the Family Constellation in the courts of justice in Brazil and themethod, it represents an advance in the humanization of law and in the expansion of citizenship in multiport courts the experiences are isolated in some judgments, and that the reduced number of well-trained constellators, the lack of qualitative and quantitative statistical monitoring are obstacles to the advancement of the institute as public policy.